P-119 'In control for what matters' living with breathlessness and low energy: video resources for patients. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Campbell, Amanda; Kidsley, Karen; Hooper, Alison
Abstract : Background: 2014 Staff Conference "Be Inspired" "An increasing ageing population… Unmet needs… Life limiting conditions, Limited resources". The message heard 'Become preventive and proactive'. Breathlessness patients who achieve self-management breath control, typically say " I am overcoming my fears and worries", "… Given me back my life ". Our patients have not stopped living and the timely access and mastery of self-management are key but do not happen only when in the presence of a health professional. Aims: How can the existing resources reach these unmet palliative care needs with empowerment and enablement? The early referral is the most proactive "…Exercise and acquiring anxiety reduction techniques is most useful early" . What will enable the early referral? Patients fear coming to the Hospice "first thought… a place people go to die". What resources will reduce these fears? Patient empowerment is necessary for success of the interventions. What resources are needed for mastery and how to make them accessible? Method: The physiotherapy team have produced short video tutorials with in-house resources for patients to use at home. The first one explains the breathlessness spiral of fears, avoidance and deconditioning, introducing upward spiral of gaining control and power. The rest of the videos have the various techniques taught in the outpatient session; thus supporting practice by the patient at home following their appointment. Results: Currently the videos are in CD format with patient feedback currently being collected. The hospice's next step is the development of a "Patient and Carer Portal" with direct links to the electronic patient record; wherever they are located, patients will be able to access their 'prescribed' videos, through the Portal. This pilot of self-help videos will be tested against measureable criteria establishing cost effectiveness accessibility compliance patient outcomes and satisfaction, impact on resources.